Nilpotency of Odd Unitary K1-Functor. Issue 8 (2nd August 2016) - Yu, Weibo; Tang, Guoping
Abstract : Using Bak's localization-completion method and a version of Stein's relativization, we obtain a descending S 0 U 2 n ( R, 𝔏)-central series S 0 U 2 n ( R, 𝔏, ℑ) ≥  S 1 U 2 n ( R, 𝔏, ℑ) ≥  S 2 U 2 n ( R, 𝔏, ℑ) ≥ …, such that S d U 2 n ( R, 𝔏, ℑ) coincides with EU 2 n ( R, 𝔏, ℑ) whenever d  ≥ Bass–Serre dimension of R . Moreover, each S d U 2 n ( R, 𝔏, ℑ) is normal in for any d  ≥ 0.